Kepatuhan Implementasi PSAK 72 pada PT Telekomunikasi Indonesia Tbk Tahun 2024 - Syahny Ramadhany; Alyn Wulandary; Musriani Musriani (Financial and Accounting Indonesian Research, 2025)
The number of investors in the Indonesian capital market has continued to grow significantly from early to mid-2024. As a publicly listed company, PT Telekomunikasi Indonesia Tbk is required to implement PSAK 72 to enhance the quality of its financial statements and demonstrate corporate responsibility through transparent disclosure of information that is useful for investors in assessing the company's financial performance, as well as in maintaining its market value. This study aims to: (1) identify the concepts and mandatory requirements for the implementation of PSAK 72 at PT Telekomunikasi Indonesia Tbk, and (2) evaluate the company's level of compliance with the concepts and mandatory requirements of PSAK 72 in 2024. This research employs a qualitative method using a case study approach, with data collected through interviews and documentation. Data analysis was conducted using open coding, axial coding, and selective coding. The findings indicate that PT Telekomunikasi Indonesia Tbk has carried out the five-step analysis required in the implementation of PSAK 72 and has established a compliance strategy to improve the company’s compliance with the standard.